PENGARUH TEKNIK COOPERATIVE LEARNING DAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR IPS - Yuono, Heru (Jurnal Pendidikan Dasar, 2015)
This study aimed to find out and analyze the effect of Numbered Heads Together (NHT) and Teams Games Tournament (TGT) technique cooperative learning and critical thinking ability on students’ learning achievement in Social Science. This study was conducted at SDN Ciwaruga 1 at Parongpong district in West Bandung with factorial experiment treatment by level 2x2 design. The sample of this study as many as 44 students was selected by random sampling technique. Data analysis took 27 % of upper group and lower group and used two path variance analysis with F test followed by Tukey test.The result of the study shows as follows: (1) as a whole, students’ learning achievement with NHT technique cooperative learning is higher than TGT technique cooperative learning with F test= 5.539 showing that it is statistically significant at the 0.05 level; (2) for high critical thinking ability students, students’ learning achievement with NHT technique cooperative learning is higher than TGT technique cooperative learning with t test= 12.22 showing that it is statistically significant at the 0.05 level; (3) for low critical thinking ability students, students’ learning achievement with TGT technique cooperative learning is higher than NHT technique cooperative learning with t test= 5.55 showing that it is statistically significant at the 0.05 level; (4) there is an interaction effect between the use of cooperative learning and students’ critical thinking ability with F test= 39.38 that it is statistically significant at the 0.05 level.It can be concluded that the effect of NHT and TGT technique cooperative learning and critical thinking ability on students’ learning achievement in Social Science at SDN Ciwaruga 1 at Parongpong district in West Bandung. Key Words: Numbered Head Together, Teams Games Tournament, Cooperative Learning, Critical Thinking Ability, Students’ Learning Achievement. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh Numbered Heads Together (NHT) dan Teams Games Tournament teknik (TGT) pembelajaran kooperatif dan kemampuan berpikir kritis terhadap prestasi belajar siswa dalam IPS. Penelitian ini dilakukan di SDN Ciwaruga 1 di Kecamatan Parongpong di Bandung Barat dengan pengobatan percobaan faktorial dengan desain tingkat 2x2. Sampel penelitian ini sebanyak 44 siswa terpilih dengan teknik random sampling. Analisis data mengambil 27% dari kelompok atas dan kelompok bawah dan menggunakan dua analisis varians jalur dengan uji F dilanjutkan dengan uji Tukey. Hasil penelitian menunjukkan sebagai berikut: (1) secara keseluruhan, prestasi belajar siswa dengan teknik NHT pembelajaran kooperatif lebih tinggi dari TGT teknik pembelajaran kooperatif dengan uji F = 5,539 menunjukkan bahwa secara statistik signifikan pada tingkat 0,05; (2) untuk kritis yang tinggi siswa kemampuan berpikir, hasil belajar siswa dengan teknik NHT pembelajaran kooperatif lebih tinggi daripada teknik TGT pembelajaran kooperatif dengan uji t = 12,22 menunjukkan bahwa secara statistik signifikan pada tingkat 0,05; (3) untuk siswa kemampuan berpikir kritis rendah, prestasi belajar siswa dengan teknik TGT pembelajaran kooperatif lebih tinggi daripada teknik NHT pembelajaran kooperatif dengan uji t = 5,55 menunjukkan bahwa secara statistik signifikan pada tingkat 0,05; (4) ada pengaruh interaksi antara penggunaan pembelajaran kooperatif dan kemampuan berpikir kritis siswa dengan uji F = 39,38 bahwa itu adalah statistik signifikan pada tingkat 0,05. Dapat disimpulkan bahwa efek NHT dan TGT teknik pembelajaran kooperatif dan kemampuan berpikir kritis terhadap prestasi belajar siswa dalam IPS di SDN Ciwaruga 1 di Kecamatan Parongpong di Bandung Barat. Kata kunci: Numbered Head Together, Teams Games Tournament, Pembelajaran Kooperatif, Kritis Kemampuan Berpikir, Prestasi Belajar Siswa.